2022
DOI: 10.3390/foods11152248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Pressure/Heating Combination on the Structure and Texture of Chinese Traditional Pig Trotter Stewed with Soy Sauce

Abstract: In order to clarify the effect of a high pressure/heating combination on the texture of Chinese traditional pig trotter with soy sauce, textural parameters (springiness, chewiness, hardness, and gumminess), the secondary structures, cross-links, decorin (DCN), glycosaminoglycans (GAGs) levels, and the histochemical morphology of collagen fibers under different treatments (0.1 MPa, 150 MPa, 300 MPa, 0.1 MPa + 50 °C, 150 MPa + 50 °C, and 300 MPa + 50 °C) were assessed. At room temperature, the 150 and 300 MPa tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Long‐time low‐temperature cooking improved the tenderness of meat products by weakening the mechanical strength of connective tissue (Latorre, Palacio, Velázquez, & Purslow, 2019), which involved the destruction of the structure of collagen fibers and the decrease of insoluble collagen content (Li et al, 2019). Also, the combined treatment of high pressure/heating could cause the collagen‐based products with soft texture by unraveling the triple‐helix structure of collagen and inducing the ultrastructural collapse of collagen fibers (Wang, Sheng, Zhang, Geng, & Cao, 2022). However, the relationship between the collagen characteristics and the texture of meat and meat products still needs to be further clarified, as Li, Ha, Warner, and Dunshea (2022) recently pointed out that collagen characteristics affected meat tenderness but varied with species, muscle, and age.…”
Section: Introductionmentioning
confidence: 99%
“…Long‐time low‐temperature cooking improved the tenderness of meat products by weakening the mechanical strength of connective tissue (Latorre, Palacio, Velázquez, & Purslow, 2019), which involved the destruction of the structure of collagen fibers and the decrease of insoluble collagen content (Li et al, 2019). Also, the combined treatment of high pressure/heating could cause the collagen‐based products with soft texture by unraveling the triple‐helix structure of collagen and inducing the ultrastructural collapse of collagen fibers (Wang, Sheng, Zhang, Geng, & Cao, 2022). However, the relationship between the collagen characteristics and the texture of meat and meat products still needs to be further clarified, as Li, Ha, Warner, and Dunshea (2022) recently pointed out that collagen characteristics affected meat tenderness but varied with species, muscle, and age.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the thermal treatments could induce a damage to the cross-links and consequently, a collapse of the collagen structure, which thus contributes to the enhancement of the textural properties (Shorthose & Harris, 2010). Our previous study has investigated an effect of a high pressure/heating combination on the texture of pig trotters and found that the treatment under the 300 MPa + 50 C improved the textual parameters, that is, springiness, chewiness, hardness, and gumminess (Wang, Sheng, Zhang, Geng, & Cao, 2022). This is highly associated with the thermal degradation of collage fibers during heating.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 17 ] demonstrated that ultrasound combined with sous-vide cooking was closely related to the improvements in the textural quality of spiced beef. Wang et al [ 18 ] demonstrated that the treatment of high pressure at 50 °C significantly improved the textural parameters of Chinese traditional pig trotter with soy sauce. However, Zhang et al [ 14 ] found that the treatment of chitosan/collagen peptides/cinnamon bark essential oil composite coating reduced some volatile compounds such as alcohols, aldehydes, ketones, and acetate during the processing of dry-aged beef, but the treatment only had a slight influence on the quality of dry-aged beef.…”
mentioning
confidence: 99%